2018
DOI: 10.1108/hff-02-2018-0041
|View full text |Cite
|
Sign up to set email alerts
|

MHD natural convection and entropy analysis of a nanofluid inside T-shaped baffled enclosure

Abstract: Purpose The purpose of this paper is to numerically study MHD natural convection and entropy generation of Al2O3-water alumina nanofluid inside of T-shaped baffled cavity which is subjected to a magnetic field. Design/methodology/approach Effect of various geometrical, fluid and flow factors such as aspect ratio of enclosure and baffle length, Rayleigh and Hartmann number of nanofluid have been considered in detail. The hydrodynamics and thermal indexes of nanofluid have been described using streamlines, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…They found that the promotion of the aspect ratio improved the circulation of dynamic flow and the Nusselt number; by contrast, an increase of the Hartmann number reduces these factors. In the same way, other studies, such as that by Armaghani et al [32], investigated the effect of the addition of a baffle to the T-shaped enclosure. They discovered that the addition of a baffle significantly enhanced the heat transfer performance inside the cavity.…”
Section: Introductionmentioning
confidence: 93%
“…They found that the promotion of the aspect ratio improved the circulation of dynamic flow and the Nusselt number; by contrast, an increase of the Hartmann number reduces these factors. In the same way, other studies, such as that by Armaghani et al [32], investigated the effect of the addition of a baffle to the T-shaped enclosure. They discovered that the addition of a baffle significantly enhanced the heat transfer performance inside the cavity.…”
Section: Introductionmentioning
confidence: 93%
“…host liquid (pure water) and nano-sized particles Fe 3 O 4 -MWCNT are in thermal equilibrium; -nanoliquid is an incompressible and Newtonian liquid; -the liquid circulation is considered to be stable and 2D; -thermal transmission is done by thermogravitational convection and the radiation influence is assumed negligible. -According to these assumptions mentioned in the physical modelling, three equations of fluid conservation, namely, conservation of mass, momentum conservation in the horizontal and vertical directions, and energy conservation are shown as follows [10,14,40]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…The effectiveness of fins has been confirmed in forced convection. However, due to reduced velocity in natural convection, the size and shape of the fin determine whether it improves or diminishes HTR, particularly in cavities [18][19][20][21][22][23][24]. Alnaqi et al [25] placed a fin of constant thermal conductivity in an inclined square cavity to investigate its effect on natural convection heat transfer.…”
Section: Introductionmentioning
confidence: 99%